Effectiveness Of Supplementation With Fe And Vitamin C Tablets On Hemoglobin Values In Female Students With Anemia - Riza Ginanjar Mustofa; Christin Jayanti; Wildan Hariri; Fikri Rizky Awali (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Anemia in adolescent girls remains a health problem that impacts decreased immunity, concentration in learning, productivity, and the risk of continuing into pregnancy. Iron tablets and vitamin C are known to increase hemoglobin formation by increasing iron absorption. Objective: To determine the effectiveness of administering iron tablets and vitamin C on hemoglobin levels in female students with anemia at STIKes RSPAD Gatot Soebroto. Method: Quantitative research with a pre-experimental one group pretest-posttest design. The sample consisted of 34 female students with anemia (Hb <12 g/dL) and were selected using consecutive sampling technique. The intervention was administration of iron tablets and vitamin C for two weeks. Data were analyzed using paired t-test. Results: Most respondents had good knowledge about anemia (59%), poor attitudes towards anemia prevention (64%), and good sleep quality (68%). The average hemoglobin level before the intervention was 10.8 g/dL (range 8.1–11.9 g/dL), while after the intervention it increased to 11.8 g/dL (range 11.5–14.5 g/dL). The results of the paired t-test showed a p value = 0.01 (<0.05), which indicated a significant increase in hemoglobin levels after administering Fe tablets and vitamin C. Conclusion: Administration of Fe tablets and vitamin C effectively increased hemoglobin levels in female students with anemia so that it can be one of the efforts to prevent and overcome anemia in adolescent girls.